Model Design of Influence of Service Quality on Customer Satisfaction in Regional General Hospitals in Gorontalo Province - Machmud, Rizan; Wolok, Tineke (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
This study aims to determine the model design of influence of service quality on customer satisfaction at Regional General Hospitals (RSUD) in Gorontalo Province. This research believes that the quality of service remains the biggest problem demanding a pattern of services to increase customer satisfaction hindering the government-owned hospital to compete with other private hospitals. This study uses AHP analysis to formulate the interest weights of various factors as the basis for the formulation of the design model, and SWOT analysis to formulate strategies by considering the importance of those factors grouped into strength (S), weakness (W), opportunities (O), and threats (T). While, the results of AHP analysis were used as the basis for each factor weighting. This study findings conclude that model design of the influence of service quality on patient satisfaction at Regional General Hospitals (RSUD) in Gorontalo Province indicating higher weight, sequentially, on assurance, tangibility, empathy, reliability, and responsiveness. Those all, undoubtedly, are essential aspects to cover as the hospitals deliberately attempt to gain patient's satisfaction. The SWOT analysis highlights that, in addition to its affordable costs and cleanliness, the hospitals were excellent as the doctors and nurses were outwardly appealing, quick-responding, kind-hearted, and communicative. The hospital weakness lies on its lack of cutlery’s cleanliness standards, unkempt inpatient rooms, nurse-doctor's sluggish coordination, ignorance, specialist unavailability, and doctors’ and nurses' incompetence. Externally, the hospital could highly grasp ample opportunities. The hospitals are referral hospitals for small communities. Their good reputation leads the public to put their trust as the population remains exponentially growing. In addition to pharmacy, the hospitals are formally accredited allowing their quality service enhancement. However, the hospitals should consider other private hospitals, customer dissatisfaction, and science and technology development as threats to their sustainable excellent service.